Peran Satuan Pengawas Ketenagakerjaan dalam Perlindungan Terhadap Pekerja Perempuan yang Bekerja Pada Malam Hari di Kabupaten Kudus - Roslila Anggraeni; Rahayu Subekti; Purwono Sungkowo Raharjo (Strata Law Review, 2023)
This research aims to determine the role and obstacles faced by labor inspectors in the context of protecting companies that employ female workers at night in Kudus Regency. This research is descriptive empirical normative research using a live case study research approach. Basically, when employing female workers at night, there are special rules regarding female workers that must be fulfilled by companies which are regulated in the Employment Law. However, its implementation is still not carried out optimally. This statement is proven by the discovery of violations committed by employers against workers, especially in employing female workers at night. This raises questions about the role of law enforcement, especially labor inspectors, in protecting female workers at night. Therefore, this writing will focus on describing the roles and obstacles faced by labor inspectors in protecting female workers at night in Kudus Regency.